Los entornos virtuales y su incidencia en el aprendizaje significativo de los niños de educación inicial de la Unidad Educativa Adolfo María Astudillo, del Cantón Babahoyo - Romero Barco, Miriam Yuleixy (2022)
The objective of this research work is to study VIRTUAL ENVIRONMENTS AND ITS IMPACT ON MEANINGFUL LEARNING, based on its classes in a virtual way, it is intended to improve the knowledge for the students of the Adolfo Maria Astudillo Educational Unit of the Babahoyo Canton, which It will help students improve their knowledge. For the development of this research, a methodological approach was applied in a descriptive and exploratory manner, which had the purpose of carrying out a survey developed in Google Meet, through which the observation and need to analyze the subject and its drawbacks was obtained as a result. , the novelty of the methodology used in this work lies in the importance of the learning environment and virtual classes, the monitoring of this project allowed us to visualize the importance of the high range of tools that the internet offers us with Conclusions and recommendations were reached for all of the aforementioned. The proposal put forward in this investigation was put into practice through a guide of activities that was carried out to improve the online knowledge process. The platform is called "Liveworksheets" and the “Kahoot” app that is available on the App store.